Staff turnover management based on HR analytics data - M.V. Chudinovskikh; A.N. Tkach; D.Y. Korolkov (Цифровые модели и решения)
Staff turnover is one of the most pressing problems faced by companies in the context of a growing shortage of staff. The article is devoted to the development of recommendations for improving staff turnover management based on HR analytics data. Based on the analysis of publications devoted to the problem of turnover, the main metrics that are used to analyze staff turnover are systematized. To expand the possibilities of justification and management decision-making, an assessment is given of the possibility of using the theory of personnel cycling, as well as a deeper study of turnover problems based on statistical methods. The developed recommendations can be used to analyze data on turnover in the company and develop measures aimed at improving the efficiency of the turnover management process.